PERAN GURU BK DALAM MENGATASI SCHOOL STRESS PESERTA DIDIK DI SMA N 11 PADANG - Rahmahdani, Nurul; Kasih, Fitria (Bimbingan dan Konseling, 2014)
The background of thos research is the students who do their homework at school, dressed unappopriate, and staying out of class when the school time still running. It is happen because the students have so many activity at school every day so they seek for the counseling teacherâs attention, so that the counseling teacher will give attention to them. There are three purposes of this research, they are: 1. The role of counseling teachers in facing individual differences, 2. The role of counseling teachers in identificating students strength and weakness, 3. The role of counseling teachersÂ  in corporating with students parents. The research is qualitative-descriptive research which has purpose to describe systematically and factually about things from certain population. It is also describing facts in detail. This research is located in SMA N 11 Padang. The informants of this research are the counseling teachers that contain of four people. Thereare also four students that help the write as the supporting informants. Data collecting method is done by doing interview, straight survey to the field, and documentation study. Then, there are three steep of analyzing,they are: 1. Data organizing, 2. Data interprenting, 3. The summary. Result of this research are: 1. The role of counseling teacher in understanding individual differences, that has done, such as distributing creativity that they have, giving compliment, being their shoulder to cry on, and helping to solve their problem, 2. The role of counseling teacher in identificating students strength and weakness, that is not run really well, such as the explanation that makes students do not what to fill the given instrument so that makes the information not complete, 3. The role of counseling teacher in corporating with students parents, that has done such as home visit. The parents show positive attitude in solving students problem. The role of counseling teacher in solving school stress of the students has run well. It is also expected that the role of counseling teachers can be more increasing to help students in solving their school stress